A suspensão da execução fiscal: pressupostos e técnicas processuais analisados sob a sistemática do modelo de processo civil atual - Cardoso, Iúri Barcellos (2023)
The purpose of the dissertation is to verify the use of the interim injuction to suspending the Execução Fiscal from the perspective of the debtor, after making use of one of the defense’s means that are conferred by the legal system, trying to avoid the executive claims expressed. The first three chapters are intended to present an overview of the current methodological stage of Civil Procedural Law, as well as to expose how the relationship between general procedural legislation and special procedural legislation takes place, the performance of procedural subjects from the perspective of the cooperative process model and the need to adapt the form of provision of judicial protection to provide legitimate and fair results. The fourth chapter was reserved to analyze the special procedure denominated Execução Fiscal and the reasons that led the legislator to create a special procedure aimed at the collection of tax credits. The fifth chapter presents an overview of the defense’s means available to the debtor and their interaction with the provisions and prerogatives granted to the Public Treasury. The sixth chapter, finally, culminates in the analysis of the judicial decision that grants or rejects the injuction required by the debtor against the executive claim, following to investigate the the nature of the referred technique and the current legal regiment reserved for it by the Código de Processo Civil de 2015. From these analyses, we sought to understand if the Superior Courts, in the sense of demanding the fulfillment of all the requirements inserted in the Código de Processo Civil de 2015’s article 919, § 1o, is fair and adequate before the systematic proposed by the current model of Brazilian civil procedure. As a result, it was possible to verify the need to attribute breadth to the techniques of provisional guardianship, because it’s techniques that aim to give maximum effectiveness to the fundamental guarantees of access to justice and, otherwise, formal restrictions would not prove to be constitutional, and could be removed through the flexibility of the procedure.